Field notes contributed by Eugene Armstrong and Eloise Armstrong, spring 1987 - Armstrong, Eloiseet al; Armstrong, Eugeneet al (1987)
List of birds and locations contributed by Eugene Armstrong and Eloise Armstrong. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of spring 1987. Epson - sheet feed/flatbed